A review of the usefulness of clinical supervisor reports when writing educational supervisor reports. Issue 4 (4th July 2019) - Bates, Suzanne; Sheldrake, Laura; Lyon-Maris, Johnny
ABSTRACT: In GP training, educational supervisors are responsible for collating evidence of a trainee's performance and progress to allow them to progress to the next stage of training. In hospital posts, they rely upon a clinical supervisor's report to help assess progress. Clinical supervisors are clinicians from various specialties who may not have an in-depth knowledge of the GP training programme, and anecdotally, our impression was that clinical supervisor reports were impersonal and not helpful in assessing a trainee's performance. We set out to evaluate the usefulness of a clinical supervisor's report in the context of completing and educational supervisor report for trainees in hospital posts. We reviewed clinical supervisor and educational supervisor reports for a cohort of 30 trainees in the Wessex Deanery, and conducted a questionnaire for their educational supervisors. All educational supervisors valued the clinical supervisor reports in completing their report, those with personal comments being the most useful. The majority of reports had a mixture of personal and generic comments. Overall, clinical supervisor reports provide additional information to evaluate performance, and they should continue to be used. To improve their use further, guidance can be given to clinical supervisors about the value of personal comments for trainees.